Criteria of livable public spaces quality. Case study analysis on the example of selected public spaces Lublin, Poland - Chęć-Małyszek, Agnieszka (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2021)
The aim of the research presented in this paper was to assess the attractiveness of selected public spaces located in the downtown of Lublin in a specific moment of time - after the experience of the Covid-19 pandemic. The research made it possible to determine the predisposition of studied spaces to be places providing peace, relaxation, tranquility in which people willingly spend their free time. At the same time, the results of the questionnaires were confronted with the surveys of spaces according to Jan Gehl's methodology of 12 Quality Criteria of Successful, Livable Space. The aim of the study was to check whether the popularization of the idea of creating a city for the people has a real impact on the realization of the newest public spaces which can be considered as new landmarks for Lublin. Selected public spaces of different kinds were analyzes according to fulfilling 12 Quality Criteria and with user’s perception survey (questionnaire).